Foreign language teaching and learning: Challenges and opportunities at Makerere University - Wagaba, William (Stellenbosch Papers in Linguistics Plus, 2011)
At Makerere University, foreign language courses in French, German and Arabic are attended by a variety of students at beginner, advanced and voluntary levels. Language students either learn foreign languages as service courses within the framework of academic programmes such as Tourism and Secretarial Studies, or as fully-fledged subjects at undergraduate level. In spite of the emphasis on language skills in job advertisements in the Ugandan press, the teaching of foreign languages tends to be oriented more towards theoretical requirements of academic (language) programmes and numbers of students, rather than toward the intensity of language contact, quality of language courses and students as well as standardised language course evaluations. The criteria for the selection of potential language students and the language learning policy are problematic and partly the cause of the unpopularity of language courses. On the basis of the evaluation of the course "German for Secretarial Studies", the current paper outlines challenges of teaching and learning German as a foreign language. There seems to be a discrepancy between the language skills that job markets require from university graduates and the skills which graduates are likely, at present, to acquire upon completion of their foreign language courses. The paper also focuses on factors that constitute barriers to foreign language learning and recommends ways in which foreign language students and teachers can exploit the potential of the budding Ugandan language industry.